PENGARUH MATA KULIAH METODOLOGI PEMBELAJARAN DAN MICRO TEACHING TERHADAP PRAKTEK PENGALAMAN LAPANGAN (PPL) DI STAIN CURUP - Siti Afifah (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
The purpose of this research  is to know a significant influence  of methodology learning  subject  variables  toward PPL, a significant influence of micro teaching  variables  toward  PPL, and  a significant influence of methodology learning  sub- ject and micro teaching  variables toward PPL students  of Prodi PAI TA. 2016/2017 in STAIN Curup.  The quantitative research method with the  type  of research  expost  facto was used  in this research. The  population was all students  of Prodi  PAI TA.2016/2017 in STAIN Curup  which consists of 177 people  with a sample  of 60 people,  and  the instruments were documenta- tion and questionnaire. The result showed  that there was a significant influence between  methodology learning subject towards PPL students  with the coefficient of determination (R square)  as 0,935,  it explained that the influence of methodology learning subject towards PPL students  was 93,5 %. Next, there was a significant influence between  micro teaching  towards PPL students with the coefficient of determination (R square)  as 0,572,  it explained that the influence of micro  teaching towards PPL students was 57,2 %. And there is a significant influence between  methodology learning subject and micro teaching  toward PPL students of Prodi PAI TA. 2016/2017 in STAIN Curup  with the coefficient of determination (R square)  as 0,935,  it explained that meth- odology  learning  subject and  micro teaching  were influenced  each  other  toward  PPL students  of Prodi PAI TA. 2016/2017 in STAIN Curup  as 93,5  %,  while the remaining 6,5 % was influenced  by other  variables  besides  methodology learning subject and micro teaching.